1978
DOI: 10.1029/jb083ib08p03955
|View full text |Cite
|
Sign up to set email alerts
|

Necking of the lithosphere and the mechanics of slowly accreting plate boundaries

Abstract: Data on ridges with slow spreading rates (1-3 cm/yr), obtained through detailed studies with Deep-Tow instruments and manned submersibles (French-American Mid-Ocean Undersea Study), or where the active structures are not submarine (Afar triangle) yield a precise picture of the axial region. There is evidence for a thinned lithosphere to be present at the axis with a thickness of 4-5 km. The thermal structure and composition of this solid layer can be estimated from seismic data and thermal and petrologic model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(97 citation statements)
references
References 78 publications
(48 reference statements)
4
93
0
Order By: Relevance
“…Artemjev and Artyushkov (1971) were probably the first to suggest that rift systems are caused by crustal thinning due to a necking instability during lithospheric extension. It was subsequently shown that lithospheric necking for slow spreading rates (1-3 cm yr −1 ) is feasible for creep flow laws considered typical for the lithosphere (Tapponnier and Francheteau, 1978). Later, the stability analysis (described above for folding) has been applied to study necking instability during lithospheric extension (Fletcher and Hallet, 1983;Ricard and Froidevaux, 1986;, including lithospheric models with two competent layers (upper crust and upper mantle) separated by a weak lower crust .…”
Section: Multilayer Neckingmentioning
confidence: 99%
“…Artemjev and Artyushkov (1971) were probably the first to suggest that rift systems are caused by crustal thinning due to a necking instability during lithospheric extension. It was subsequently shown that lithospheric necking for slow spreading rates (1-3 cm yr −1 ) is feasible for creep flow laws considered typical for the lithosphere (Tapponnier and Francheteau, 1978). Later, the stability analysis (described above for folding) has been applied to study necking instability during lithospheric extension (Fletcher and Hallet, 1983;Ricard and Froidevaux, 1986;, including lithospheric models with two competent layers (upper crust and upper mantle) separated by a weak lower crust .…”
Section: Multilayer Neckingmentioning
confidence: 99%
“…Figure 9 shows detailed bathymetry for a few ridge segments within this section. Slowspreading ridges such as the northern MAR are marked by a 1.5-3 km-deep, 30 -45 km-wide axial rift valley (Tapponnier & Francheteau 1978;Macdonald 1986). An inner valley floor (5-12 km wide) is bordered by valley walls in which large (hundreds of metres) inward-facing normal faults displace the crust upwards to form the crestal mountains.…”
Section: Slow-spreading Ridgesmentioning
confidence: 99%
“…These offsets divide the ridge axis into individual spreading segments with lengths ranging from 10 to 100 km (e.g., Macdonald, 1986;Sempéré et al, 1993). The steady-state topography of a slow-spreading ridge is characterized by a prominent axial valley 10-0 km wide and 1-3 km deep (Macdonald and Atwater, 1978;Karson et at., 1987;Grindlay et at., 1992;Sempéré et al, 1993) and is consistent with a lithospheric necking model (e.g., Tapponnier and Francheteau, 1978;Phipps Morgan et al, 1987;Phipps Morgan and Chen, 1993;Shaw and Lin, 1996). Axial depth typically shallows toward the center of a ridge segment, with transform and NTOs intersecting the axis in topographic depressions at the segment ends.…”
Section: Introductionmentioning
confidence: 54%